Obtenção de sachês biodegradáveis de amido reforçados com nanopartículas de CuO para liberação de nutrientes minerais - Malafatti, João Otávio Donizette (Universidade Federal de São Carlos, 2020)
Fertilizers have been used as agricultural inputs to allow maximum yield during the growth of crops. One of the significant challenges is the efficiency of the plant's nutritional process. It is necessary to use excessive amounts of nutrients to minimize losses due to leaching and aerial dispersion processes, leading to economic and environmental contamination. Potassium is one of the essential fertilizers used in agriculture, and like the others, it is mainly provided by import. Thus, the present research project aimed to develop biodegradable starch sachets for packaging and potassium fertilizer release. However, starch materials are subject to the loss of initial characteristics due to the degenerative retrogradation effect, high hygroscopicity, and easy proliferation of microorganisms, decreasing the shelf life until application in the field. In this sense, for the best performance, the presence of citric acid was evaluated, aiming at the esterification of starch and the insertion of faujasite zeolite (FAU) reinforcement materials modified with Cu2+ and CuO nanoparticulate ions. Copper is one of the micronutrients used to develop plants and presents antimicrobial properties, enabling more remarkable preservation of sachets. The CuO nanoparticles and the FAU were obtained by quicky precipitation and the hydrothermal treatment methods, respectively. The processing of the films that make up the sachet was carried out from the homogenization of the starch under temperature, in the presence of water and urea, acting as plasticizer and source of nitrogen for the plants, followed by thermo-pressing. In the starch films, it was possible to obtain a matrix with 25% (w/w) of urea, enabling the polymeric matrix to be more ductile. When inserting the reinforcement materials, it was possible to verify that CuO at a concentration of 1% (w/w) showed an increase in tensile strength of about 120%, a result similar to that found for the FAU reinforced film in the concentration of 3% (w /w) and with the presence of citric acid. All copper-containing films showed a fungistatic effect for the fungus Alternaria alternata, a microorganism very susceptible to sources rich in carbohydrates. Besides, the film containing 1% (w/w) CuO of nanoparticles showed protection against visible and ultraviolet radiation. In the release of KCl in sachets, it was possible to observe K+ ions rapid availability when coming into direct contact with the aqueous medium, thus enabling a quick action with the external medium. Upon the release of urea, all sachets showed a similar value after 60 days, indicating equivalent matrix degradation. For the Cu2+ nutrient, it was possible to observe that the FAU film with citric acid below releases the ion, possibly due to the more stabilization of the cation in the matrix. In this way, starch sachets were obtained with promising properties that increase fertilizer commercial application viability.
Obtaining biodegradable starch sachets reinforced with CuO nanoparticles to release mineral nutrients
Keywords: Amido; Óxido de cobre; Fertilizante; Faujasita; Filmes; Nanocompósito; Sachês; Potássio; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS::MATERIAIS CONJUGADOS NAO METALICOS; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA